Vivid structural colors with low angle dependence from long-range ordered photonic crystal films. Issue 9 (13th December 2016) - Su, Xin; Xia, Hongbo; Zhang, Shufen; Tang, Bingtao; Wu, Suli
Abstract : Vivid structural colors with low angle dependency were obtained by fabricating highly ordered photonic crystal films using monodisperse spheres with a high refractive index as building blocks. Abstract : Structural colored materials have attracted increasing attention due to their vivid color effects and non-photobleaching characteristics. However, the angle dependence of these structural colors severely restricts their practical applications, for example, in display and sensing devices. Here, a new strategy for obtaining low angle dependent structural colors is demonstrated by fabricating long-range ordered photonic crystal films. By using spheres with high refractive indices as building blocks, the angle dependence of the obtained colors has been strongly suppressed. Green, golden yellow and red structural colored films with low angle dependence were obtained by using 145 nm, 165 nm and 187 nm Cu2 O spheres as building blocks, respectively. SEM images confirmed the long-range highly ordered arrays of the Cu2 O photonic crystal films. Reflectance spectra and digital photographs clearly demonstrate the low angle dependence of these structural colors, which is in sharp comparison with the case of polystyrene (PS) and SiO2 photonic crystal films. Furthermore, these structural colors are vivid with high color saturation, not only under black background, but also under white background and natural light without adding any light-absorbing agents. These low angle dependent structural colors endow Cu2 O photonic crystal films with great potential in practical applications. Our findings may broaden the strategies for the design and fabrication of angle independent structural colored materials.